Strong and Tough Bioinspired Additive-Manufactured Dual-Phase Mechanical Metamaterial Composites. (April 2021) - Yin, Sha; Guo, Weihua; Wang, Huitian; Huang, Yao; Yang, Ruiheng; Hu, Zihan; Chen, Dianhao; Xu, Jun; Ritchie, Robert O.
Highlights: Bioinspired dual-phase metamaterials are designed with lattice materials as constituent phases Stiffness, strength, toughness and specific energy absorption are all increased after reinforcement-phase additions Effects of reinforcement phase patterning and connectivity are examined Optimized dual-phase materials with a maximum phase-boundary slip area exhibit the highest specific energy absorption A design rationale for dissipative dual-phase metamaterials is proposed Abstract: Nature's materials are generally hybrid composites with superior mechanical properties achieved through delicate architectural designs. Inspired by the precipitation hardening mechanisms observed in biological materials as well as engineering alloys, we develop here dual-phase mechanical metamaterial composites by employing architected lattice materials as the constituent matrix and reinforcement phases. The composite metamaterials made from austenitic stainless steel are simply fabricated using selected laser melting based additive manufacturing. Using quasi-static compression tests and simulation studies, we find that strength and toughness can be simultaneously enhanced with the addition of reinforcement phase grains. Effects of reinforcement phase patterning and connectivity are examined. By fully utilizing the energy dissipation from phase-boundary slip, an optimized dual-phase metamaterial is designed with the maximum slip area, where every truss unit in the matrix phase is completely surrounded by reinforcement phase lattices; this material exhibits a specific energy absorption capability that is 2.5 times that of the constituent matrix phase lattices. The design rationale for dissipative dual-phase metamaterials is analyzed and summarized with a focus on phase pattering. The present digital multi-phase mechanical metamaterials can emulate almost any of nature's architectures and toughening mechanisms, offering a novel pathway to manipulate mechanical properties through arbitrary phase-material selection and patterning. We believe that this could markedly expand the design space for the development of future materials.